Evaluating pelvic floor muscle contractility using two‐dimensional transperineal ultrasonography in patients with pelvic organ prolapse. Issue 5 (1st April 2019) - Ouchi, Mifuka; Kitta, Takeya; Suzuki, Shigeyuki; Shinohara, Nobuo; Kato, Kumiko
Abstract: Aim: The hiatal anterior‐posterior distance (APD), as measured by two‐dimensional (2D) transperineal ultrasonography, is an indicator of pelvic floor muscle (PFM) contractility. The function of the pelvic floor is independently related to pelvic organ prolapse (POP) severity. However, little evidence concerning the APD for patients with POP before and after PFM training (PFMT) has been published. Therefore, we analyzed 2D transperineal ultrasonography in women with POP. Methods: Twenty‐eight women with POP completed a physiotherapist‐led PFMT regimen that consisted of 4 months of one‐on‐one PFMT and lifestyle advice. The APD was measured using 2D transperineal ultrasonography immediately before and after the PFMT period and used to calculate ΔAPD (APD at rest—APD during contraction). Vaginal squeeze pressure during maximum voluntary contractions was also assessed using a manometer. We then analyzed the reliability and the correlation between ΔAPD as measured using 2D transperineal ultrasonography and vaginal squeeze pressure before and after PFMT. Results: The APD at rest and during PFM contractions demonstrated intraclass correlation coefficients (ICCs) of 0.89 and 0.88, respectively. The ICC of maximal vaginal squeeze pressure was 0.97 during PFM contractions. Both ΔAPD ( P < 0.01) and PFM strength ( P < 0.05) increased significantly after PFMT. PFM strength and ΔAPD were correlated before ( R = 0.53) and after ( R = 0.68) PFMT ( P < 0.01). Conclusions: We demonstrated that dynamic 2D transperineal ultrasonography could be used for studying functional changes in patients with POP. The ΔAPD of the levator hiatus has potential as an anatomical surrogate marker for evaluating PFM function in hospitals.